PEMANFAATAN AKUN INSTAGRAM @bemkmipb_edu SEBAGAI SARANA KOMUNIKASI DAN INFORMASI YANG MENDUKUNG KEBUTUHAN MAHASISWA IPB - Niswatun Choirina, Nora; Ghozali Meonawar, Mohamad; Dharmawan, Leonard; Manisya, Nabhila; Azzahra, Maharani (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
Advance in digital technology have changed the communication system, shifting from conventional media to social media which is faster and more efficient in disseminating information. Social media has now become the main platform that supports information needs, especially for students in academic environments. This research aims to analyze how the @bemkmipb_edu account utilizes the Instagram platform as a means of communication and information that supports the needs of IPB students. This research uses a qualitative approach which involves collecting data by interviewing key informants and informants, using Lasswell's communication theory. The research results show that Instagram is the optimal media thanks to its popularity among students, ease of access, and visual features that support the delivery of information quickly and interestingly.